2012
DOI: 10.1182/blood-2011-02-333435
|View full text |Cite
|
Sign up to set email alerts
|

CBL mutation in chronic myelomonocytic leukemia secondary to familial platelet disorder with propensity to develop acute myeloid leukemia (FPD/AML)

Abstract: IntroductionFamilial platelet disorder with a propensity to develop acute myeloid leukemia (FPD/AML) is a rare autosomal dominant disease characterized by thrombocytopenia, abnormal platelet function, and a propensity to develop myelodysplastic syndrome (MDS) and AML. 1,2 Since Song et al reported haploinsufficiency of the RUNX1/CBFA2 gene, 3 more than 20 affected families have been reported. [4][5][6][7][8] Notably, various types of mono-allelic mutations of the RUNX1 gene have been found in patients with AML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…151,152 In addition, FPD/AML patients may develop other types of leukemias, such as T-ALL, Hairy cell leukemia (HCL), and CMML. 151,[153][154][155] Interestingly, higher incidence of MDS and AML have been observed in families with certain types of mutations. 148,151 The exact mechanism of thrombocytopenia and leukemia in FPD/AML patients is not clear.…”
Section: Familial Platelet Disorder With Predisposition To Acute Myelmentioning
confidence: 99%
See 1 more Smart Citation
“…151,152 In addition, FPD/AML patients may develop other types of leukemias, such as T-ALL, Hairy cell leukemia (HCL), and CMML. 151,[153][154][155] Interestingly, higher incidence of MDS and AML have been observed in families with certain types of mutations. 148,151 The exact mechanism of thrombocytopenia and leukemia in FPD/AML patients is not clear.…”
Section: Familial Platelet Disorder With Predisposition To Acute Myelmentioning
confidence: 99%
“…160 In addition, cooperating somatic mutations in more than 20 genes and copy number changes are observed in MDS and leukemic samples from FPD/AML patients. 154,155,162,164-169 ASXL1, CBL, CDC25C, FLT3, PHF6, SRSF2, and WT1 were identified as recurrently mutated genes. Additional studies using unbiased genomic approaches are required to identify recurrently mutated genes that cooperate with RUNX1.…”
Section: Familial Platelet Disorder With Predisposition To Acute Myelmentioning
confidence: 99%
“…62 However, this mutation could not be detected by other investigators. 60, 63 This could represent ethnic differences. The number of mutations in the blast cells found at the time of AML varies between 8 and 18.…”
Section: Preleukemia: Germline Mutant Hematopoietic Clonementioning
confidence: 99%
“…CBL mutations have also been identified in the patients with FPD/AML. Shiba et al reported that CBL mutation and 11q-acquired uniparental disomy (11q-aUPD) cooperate with RUNX1 mutation to develop CMML [36].…”
Section: Additional Genetic Events For Mutant Clone Expansion and Leumentioning
confidence: 99%